A Review of Gastric Polyps - Chowdhury, Abu Taiub Mohammed Mohiuddin; He, Shuixiang; Wang, Ru Hua; Guo, Dan; Li, Yarui (Journal of Digestive Endoscopy, 2019)
Gastric lesions presenting as polyps becomes common these days. Many different underlying causes have been suspected with the origin of gastric polyps. Generally, a gastric polyp is considered as benign in the first impression unless proven otherwise. Though, they show a vast variety of malignant potentials. This literature is intended to describe and evaluate the variations, presentations, features, and potentials of gastric polypoid lesions.
Keywords: gastric polyp; fundic gland polyps (FGP); hyperplastic polyps; inflammatory fibroid polyps; gastric neuroendocrine tumors (NETs); granular cell tumor (GCT); gastrointestinal stromal tumors (GISTs); ectopic pancreas